Detecting land use/land cover changes in the Lake Hayq (Ethiopia) drainage basin, 1957–2007. Issue 1 (March 2015) - Yesuf, Hassen M.; Assen, Mohammed; Melesse, Assefa M.; Alamirew, Tena
Abstract: Land use/land cover changes in a lake drainage basin reflect changes in the magnitude of the water balance components and rate of sediment deposition in a lake as a reflection of the fundamental linkage between what happens in a lake considered against what is happening in the drainage basin of the lake. The objective of this study was to quantify the spatio‐temporal land cover/land use changes across the Lake Hayq1 closed drainage basin in north‐east Ethiopia over a 50‐years period, using multitemporal remote sensing and geospatial data. Two historical occasions of aerial photographs (1957 and 1986) and one satellite image (2007) were examined with image analysis tools: Leica Photogrammetric Suite (LPS 9.2) Project Manager, ArcGIS10.0, and ERDAS EMAGINE 9.2. Seven aerial coverage of land use/land cover categories were identified and mapped for the past three historical times. The results indicated that farmlands/settlements and shrublands/degraded lands increased by 43.1% and 136.9%, at an annual rate of 27.4 and 13.5 ha year −1, respectively, between 1957 and 2007. In contrast, bushlands, grasslands, forestlands and lake surface area were diminished by 68.8%, 62.7%, 90.5% and 7.6%, at a rate of 24.0, 7.6, 6.1 and 3.7 ha year −1, respectively, over the past five decades. The basin had undergone significant transformation in land use/land cover over the past half century, affecting the lake's biophysical stability by accelerating soil erosion in the basin, sediment accumulation, and a reduced quantity and quality of cumulative stream flow into the lake.